2021
DOI: 10.1088/1748-605x/ac3620
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effects of the immobilization of SEMA4D on titanium surfaces in an endothelial cell/macrophage indirect coculture model

Abstract: In this study, we established a procedure to prepare a Semaphorin4D (SEMA4D)-immobilized titanium surface and explored its effects on macrophage behaviors in an endothelial cell/macrophage indirect coculture model. The SEMA4D-bovine serum albumin complex was immobilized onto a preprocessed poly L-lysine titanium surface through NaOH hydrothermal treatment and self-assembly technology. All titanium specimens were examined for surface microstructure, surface element composition, and surface wettability by field … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 85 publications
0
2
0
Order By: Relevance
“…In addition, sSema4D activates platelets, mediates angiogenesis, and accelerates plaque growth and instability (30,31). A previous study showed that sSema4D downregulated the expression of pro-inflammatory cytokines in macrophages because it weakened the NF of THP-1 macrophages stimulated by lipopolysaccharide-κ activation of B signal pathway (32).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, sSema4D activates platelets, mediates angiogenesis, and accelerates plaque growth and instability (30,31). A previous study showed that sSema4D downregulated the expression of pro-inflammatory cytokines in macrophages because it weakened the NF of THP-1 macrophages stimulated by lipopolysaccharide-κ activation of B signal pathway (32).…”
Section: Discussionmentioning
confidence: 99%
“…SEMA4D is the first signaling element to play a role in the immune system (25). It exists in a soluble functional form that can bind to multiple receptors involved in immune regulation and inflammatory responses (26).…”
Section: Survival Timementioning
confidence: 99%